Analysis of The Influence Brand Image on Community Purchase Intention in Outpatient Services at Bima City Hospital - Dimara, Fransiska Natalia; Nurhidayati, Restu; Wulandari, Ratna Dwi; Pudjirahardjo, Widodo J. (Universitas Malahayati, 2025)
ABSTRACT Hospitals face competitive competition due to open market policies in the medical services industry. In the realm of health services, brand image plays an important role in determining patient purchase intentions. Therefore, the aim of this study is to analyze the influence brand image on community purchase intention in outpatient services in government hospitals. An analytical study with a cross-sectional approach was was carried out by distributing questionnaires in Bima from October 2022 to July 2023. The population of this study were people related to hospital services with good awareness and aged 19 -60. The sample was selected using the proportional stratified random sampling method. Descriptive statistics and correlation analysis were used to analyze the data. A total of 260 respondents from five sub-districts participated in the study. The results showed that brand image had a significant effect on the community's purchase intention towards outpatient services. Influential brand image indicators are type of brand associations with value (p = 0.486 b = 0.001), favorability of brand association with value (p = 0.198 b = 0.001) and uniqueness of brand associations with value (p = 0.165 b = 0.001). A good brand image can increase purchase intention. The brand image sub-variable that has the greatest influence on purchase intention is the type of brand associations. There was one item that was rated as poor by 60.4% of respondents regarding the timeliness of doctor services in outpatient care. A good brand image can increase purchase intentions. Evaluation and coordination between management and service providers are necessary to improve the hospital's brand image. Related activities and service schedules of doctors in the hospital must be well organized so that there is no doctor's absence. Keywords: Brand Image, Hospital, Outpatient Service, Purchase Intention